Geriatric Inguinal Hernia and its Surgical Management â€“ Findings From a Retrospective Study - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The objective of the study was to study the surgical management of inguinal hernia (groin hernia) among geriatric (elderly) patients. Materials and Methods: A retrospective study was conducted from December 2016 to August 2018 in the surgical ward of a university hospital in Malaysia. Geriatric patients operated for surgery during the study period were recruited in the study. A total of 116 cases operated for groin hernia with or without comorbidities and their influence on the overall results of surgical interventions were studied. Results: The mean age of the patients was 71.02 Â± 3.1 years, of whom 94 (81%) were male and 22 (19%) were female. In 66 (56.9%) patients, the hernias were simple, while 21 (18.1%) had an obstructive inguinal hernia. In 17 (14.7%) patients, the hernia was incarcerated while 12 cases presented had strangulations. Comorbidities were present in 97 (83.6%) patients. No mortality was found either in elective or in emergency surgery. Conclusion: Comorbidities, type of surgery (elective or emergency), type of hernia (simple or complicated), and age of the patients can make surgery more challenging in the geriatric population.